Malignant catarrhal fever-like lesions associated with ovine herpesvirus-2 infection in young calves (Bos indicus): a case report - Luvizotto, M. C. R. [UNESP] (2010)
Infection of susceptible ruminants, including domestic cattle (Bos taurus) and American bison (Bison bison), with ovine herpesvirus-2 (OvHV-2) may provoke the fatal vasculitis and lymphoproliferative syndrome, known as malignant catarrhal fever (MCF), reported worldwide. To the best of our knowledge, this is the first report of a clinical case of MCF-like lesions associated with ovine herpesvirus-2 (OvHV-2) infection in young calves (Bos indicus) including central nervous symptoms that occurred in Tres Lagoas city, Mato Grosso do Sul state, a border town near São Paulo state, Brazil. The diagnosis was based on typical histological lesions characterized by systemic lymphohistiocytic and fibrinoid vasculitis, confirmed by polymerase chain reaction and subsequent phylogenetic analysis of detected OvHV-2 sequences. This finding indicates that MCF disease is spread among herds concentrated in border areas between Mato Grosso do Sul and São Paulo states.